Patient focused drug surveillance on elderly patients with chronic diseases in nursing homes - Olsson, Inger Nordin (Igitur, Utrecht Publishing & Archiving, 2008)
BACKGROUND: Modern drugs have made great contributions to better quality of life, less disabling symptoms, decreased demands of health care and a better prognosis. Despite this, one can nowadays notice an increasing proportion of negative side effects and adverse drug reactions due to extensive pharmacological treatment. STUDY OBJECTIVES: To examine if patient-focused drug surveillances were associated with a higher quality of drug treatment at nursing homes? METHODS: Physicians were told to systematically focus on the patient's basic health status as a fundamental starting point for further continuous medication, with the aim to obtain a rational drug usage. SETTING: An intervention study in nursing homes in Sweden. OUTCOMES: Mortality, health care consumption and number of drugs. Health status and evaluation of drug therapy. RESULTS: No significant difference in mortality rate. Extensive health care consumption in both groups. Significant differences of examinations like weight, blood pressure and renal function. Monitoring and evaluation of medications showed significant differences favouring the intervention group. Due to existing polypharmacy there was a significant reduction of number of drugs in the intervention group vs. a significant increase in the control group. CONCLUSIONS: The intervention seemed to have achieved significant positive results in ‘quality of drug treatment’, although it has shown immense lacks of monitoring the health status of frail elderly.